A Richardson-Lucy Algorithm Based Blind Deconvolution to Decouple the Two Unknown Spatial-Temporal SRAM Margin Variations - H. Yamauchi; Worawit Somha (Journal of Physics Conference Series, 2023)
Abstract A Richardson-Lucy algorithm (RLA) based blind deconvolution with a new filter design technique was successfully developed. This allowed decoupling and retrieving of the information of the two unknown factors at once for the Random Temporal Variation (RTV) and the Random Spatial Variation (RSV). The variations of SRAM operating voltage (V DDMIN ) are caused by the two coupled factors of RTV and RSV. Thus, this decoupling technique is prerequisite for the margin analysis. The designs of the device characteristics and the screening test conditions based on the analysis results were briefly demonstrated. The proposed filter design technique for the RLA based blind deconvolution allowed to circumvent the ill-conditioning ringing phenomena. This gives to enjoy the advantage in convergence speed and simplicity of the RLA. The relative errors of the blind-deconvolution for the RSV and RTV distributions were reduced to less than 0.3% within only 300-iteration cycles compared with the conventional one.
Keywords: Blind Source Separation Techniques; Non-Destructive Testing Techniques; Integrated Circuits and Semiconductor Failure Analysis